PENGARUH LAMA MELAUT DAN JUMLAH HAULING TERHADAP HASIL TANGKAPAN IKAN PADA PERIKANAN GILLNET SKALA KECIL DI PEKALONGAN JAWA TENGAH - Wiyono, Eko Sri (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The high competition among fishermen have resulted decreasing fish catches. To ensure the continuity of his activity, fishermen perform a variety of fishing strategies such as adding a length time of fishing trip at the sea and increasing the number of hauling. To assess the impact of both factors have been conducted research on gillnet small-scale fisheries (